A Novel TRIM9 Protein Promotes NF-κB Activation Through Interacting With LvIMD in Shrimp During WSSV Infection - Sun, Mingzhe; Li, Shihao; Jin, Songjun; Li, Xuechun; Xiang, Jianhai; Li, Fuhua (Frontiers in Immunology, 2022)
The TRIpartite Motif (TRIM) proteins play key roles in cell differentiation, apoptosis, development, autophagy and innate immunity in vertebrates. In the present study, a novel TRIM9 homolog (designated as LvTRIM9-1) specifically expressed in the lymphoid organ of shrimp was identified from the Pacific whiteleg shrimp Litopenaeus vannamei. Its deduced amino acid sequence possesses the typical features of TRIM proteins, including a RING domain, two B-boxes, a coiled-coil domain, a FN3 domain, and a SPRY domain. The transcripts of LvTRIM9-1 were mainly located in the lymphoid tubules of the lymphoid organ. Knockdown of LvTRIM9-1 could apparently inhibit the transcriptions of some genes from white spot syndrome virus (WSSV) and reduce the viral propagation in the lymphoid organ. Over expression of LvTRIM9-1 in mammalian cells could activate the promoter of NF-κB, and in vivo experiment in shrimp showed that knockdown of LvTRIM9-1 reduced the expressions of LvRelish in lymphoid organ. Yeast two-hybridization and Co-immunoprecipitation (Co-IP) assays confirmed that LvTRIM9-1 could directly interact with LvIMD, a key component of the IMD pathway, through its SPRY domain. These data suggest that LvTRIM9-1 could activate the IMD pathway in shrimp via interaction with LvIMD. This is the first evidence to show the regulation of a TRIM9 protein on the IMD pathway through its direct interaction with IMD, which will enrich our knowledge on the role of TRIM proteins in innate immunity of invertebrates.